Inequalities in children’s tooth decay requiring dental extraction under general anaesthetic: a longitudinal study using linked electronic health records - Carol Dezateux; Nicola Firman; Vanessa Muirhead (BMJ Public Health)
Background Dental extraction under general anaesthetic (DGA) is the most severe and irreversible dental treatment for childhood tooth decay. We investigated inequalities in DGA in an ethnically diverse, disadvantaged school-age population and associations of DGA with prior excess weight.Methods We identified 608 278 children aged 5–16 years in 2017–2022 from linked hospital and primary care electronic health records (EHRs) for a London, UK region. We estimated ORs (95% CI) for DGA, adjusting for sex, ethnicity, locality and deprivation. We linked 120 985 EHRs to school weight records and estimated HRs (95% CI) for DGA by excess weight (body mass index ≥91st centile) using Cox’s proportional regression.Results 3034 children had at least one DGA (0.50%; 95% CI 0.48 to 0.52). Children from white Irish (OR: 1.96; 95% CI 1.17 to 3.29), other Asian (1.23; 95% CI 1.01 to 1.50), Bangladeshi (1.49; 95% CI 1.30 to 1.70) and Pakistani (1.41; 95% CI 1.21 to 1.65) ethnicities were more likely and those from Chinese (0.48; 95% CI 0.27 to 0.86), white and black African (0.59; 95% CI 0.35 to 0.98), other mixed (0.69; 95% CI 0.50 to 0.95), Indian (0.65; 95% CI 0.53 to 0.81), black African (0.79; 95% CI 0.66 to 0.93) and other black (0.62; 95% CI 0.48 to 0.82) ethnicities and living in less deprived areas less likely, to have had a DGA. Five- (HR: 0.80; 95% CI 0.66 to 0.94) and 11- year-olds (0.78; 95% CI 0.62 to 0.99) with excess weight were less likely to have had a DGA.Conclusion We found marked ethnic and socioeconomic inequalities in childhood DGA. Further research is needed to understand factors mediating inequalities in DGA. These findings emphasise the importance of targeting the wider determinants of inequalities in tooth extraction and ensuring equitable access to preventive and restorative dentistry.